Nuclear magnetic resonance (NMR) spectroscopy - SathishKumar, R. (Elsevier Inc., 2017)
Nowadays, nuclear magnetic resonance (NMR) spectroscopy is one of the most essential research tools in material science and engineering. It received a considerable interest in membrane technology that offers structural information [1], blend miscibility [2], blend phase morphology [3], and purity of polymers [4]. It provides details about the stability and degradation of the polymers such as degree of acetylation, degree of amination, and degree of sulfonation [5-8]. It is also used to predict the pore size distributions of the polymer matrix [9]. The main objective of this book chapter is to increase our knowledge of using NMR spectroscopy on membrane technology. In addition, the chemical nature and the surface features of polymeric membranes and their proton conductivity properties were correlated.